1996
DOI: 10.1007/s002689900166
|View full text |Cite
|
Sign up to set email alerts
|

Application of Formaldehyde for Treatment of Hemorrhagic Radiation‐Induced Proctitis

Abstract: Radiation-induced proctitis with hemorrhage is not a common complication of radiotherapy to the pelvis for carcinoma. In the most severe forms, massive hemorrhage may necessitate repeated transfusions and inpatient treatment. In severe cases medical treatment has not been proved effective. Surgery may lead to serious complications and is technically difficult. Six patients who showed a hemorrhagic radiation-induced proctitis have been treated as outpatients with application of formaldehyde 4%. In four cases th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 20 publications
3
42
0
1
Order By: Relevance
“…11,64 In several small, nonrandomized studies, the short-term success rate of this technique ranged from 60% to 100%. [66][67][68][69][70][71][72][73] The documented complications, including perianal ulcerations and fissures, anal stenosis, and fecal incontinence, occurred in 27% of patients.…”
Section: Topical Formalinmentioning
confidence: 99%
“…11,64 In several small, nonrandomized studies, the short-term success rate of this technique ranged from 60% to 100%. [66][67][68][69][70][71][72][73] The documented complications, including perianal ulcerations and fissures, anal stenosis, and fecal incontinence, occurred in 27% of patients.…”
Section: Topical Formalinmentioning
confidence: 99%
“…Local application of 4% formaldehyde has been used with greater therapeutic success in some studies (Table 2). 12,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] Evidence suggests that formalin is very effective in the treatment of CHRP, mainly in patients in whom the distal third of the rectum is affected. Other advantages of formalin application are low cost, low incidence of side-effects, ready availability, and easy application.…”
Section: Formalinmentioning
confidence: 99%
“…11 It occurs among 5-20% of patients in the form of bleeding, fistula, ulceration and strictures. 12 It presents as rectal bleeding, diarrhea, mucus discharge, tenesmus, incontinence and urgency. In an assessment of 90 patients with radiation damage to the rectosigmoid, den Hartog Jager et al found that rectal bleeding was the main presenting complaint in up to 72% of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Silver nitrate, an inorganic silver salt, induces a chemical cauterization and has been used to control bladder hemorrhages and epistaxis [12,23]. Formalin, 2% or 4%, acts as a chemical cautery and has been used to control intractable rectal [24][25][26] and bladder [22] hemorrhaging. In one case series, topical formalin controlled bleeding in 49 of 55 patients (89%) with radiationinduced rectal bleeding.…”
Section: Etiology and Clinical Presentationmentioning
confidence: 99%